Internet Resources for Water - Robert J. Teeter (Issues in Science and Technology Librarianship, 1997)
Like water itself, the science of water flows in all directions -- hydrology, hydraulics, geology, meteorology, oceanography, environmental science, engineering, and law. Water scientists and engineers need information on specific locations and general principles. The following Internet resources are some of the most useful on water and related subjects.